Wpływ leczenia usprawniającego na rozwój ruchowy pacjentki z chondrodysplazją przynasadową typu Schmida - opis przypadku - Skworc, Aneta; Osiadło, Grażyna; Sławska, Helena; Jezela-Stanek, Aleksandra; Marciniak, Sylwia (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Schmid type metaphyseal chondrodysplasia is an autosomal dominant genetic disease. MCDS is a rare disorder and the presented case, to our knowledge, is the only Polish case with a conńrmed and novel mutation of COL10A1 gene. Since the girl reached the age of 2 years and 7 months, she has been applied a systematic neurodevelopmental physiotherapy influencing the posture. The aim of the research was to assess the quality of posture control conducted before and after annual neurodevelopmental therapy. Over that period of time, the posture was assessed by means of the point-based method according to Kasperczyk and the distance of gait was determined. Comparative analysis of X-ray pictures of femoral joints and lower extremities was conducted. Moreover, the posture and gait of the child were videotaped. The results have led to the conclusion that the use of the chosen methods and neurodevelopmental techniques in postural control disorders in children with rare genetic diseases is accurate.